Ovine PrP transgenic Drosophila show reduced locomotor activity and decreased survival - Thackray, Alana M.; Jahn, Thomas R.; Evers, Jan-Felix (Biochemical journal, 2012)
Drosophila have emerged as a model system to study mammalian neurodegenerative diseases. In the present study we have generated Drosophila transgenic for ovine PrP (prion protein) to begin to establish an invertebrate model of ovine prion disease. We generated Drosophila transgenic for polymorphic variants of ovine PrP by PhiC31 site-specific germ-line transformation under expression control by the bi-partite GAL4/UAS (upstream activating sequence) system. Site-specific transgene insertion in the fly genome allowed us to test the hypothesis that single amino acid codon changes in ovine PrP modulate prion protein levels and the phenotype of the fly when expressed in the Drosophila nervous system. The Arg154 ovine PrP variants showed higher levels of PrP expression in neuronal cell bodies and insoluble PrP conformer than did His154 variants. High levels of ovine PrP expression in Drosophila were associated with phenotypic effects, including reduced locomotor activity and decreased survival. Significantly, the present study highlights a critical role for helix-1 in the formation of distinct conformers of ovine PrP, since expression of His154 variants were associated with decreased survival in the absence of high levels of PrP accumulation. Collectively, the present study shows that variants of the ovine PrP are associated with different spontaneous detrimental effects in ovine PrP transgenic Drosophila.